PENGARUH HUMAN CAPITAL, RELATIONAL CAPITAL DAN ORGANIZATIONAL CAPITAL TERHADAP KINERJA PEGAWAI (Studi pada Badan Ketahanan Pangan Provinsi Sumatera Barat) - Yuli Ramanda; Bustari Muchtar (Program Studi Magister Manajemen, 2015)
The purpose of this research is to determine the effect of human capital, relational capital, and organizational capital toward employee performance, human capital toward relational capital and organizational capital and relational capital toward organizational capital. This research is conducted using a survey method, sample and questionnaire as a primary data collection. This research take place in the Board Food Security (Badan Ketahanan Pangan) of West Sumatera with a number of respondents is 101. Structural Equation Modeling (SEM) was used to analyze the model with the help of the program AMOS 20.0. The results show that there is a significant effect of human capital on relational capital and of relational capital on organizational capital. But there was no significant effect of human capital, relational capital, and organizational capital on employee performance. Keywords: human capital, relational capital, organizational capital, employee performance.